Vračanje na delo po operaciji zaradi zdrsa medvretenčne ploščice v ledvenem delu hrbtenice - Potočnik, Veronika (Rehabilitacija (Ljubljana), 2016)
Background: Lumbar disc herniation (LDH) is a common problem of the economically active population. Surgery is a treatment of choice. Return to work is considered as important long-term surgical outcome. The aim of this study was to analyse the rate of return to work after surgical treatment of LDH and
Keywords: delazmožnost; lumbar disc herniation; Lumbar Vertebrac; operacija; rehabilitacija; Rehabilitation, vocational; surgery; vocational rehabilitation; work ability; zdrs medvretenčne ploščice